2022
DOI: 10.1021/jacs.1c11022
|View full text |Cite
|
Sign up to set email alerts
|

Triplet–Triplet Annihilation Photopolymerization for High-Resolution 3D Printing

Abstract: Two-photon polymerization (TPP) currently offers the highest resolution available in 3D printing (∼100 nm) but requires femtosecond laser pulses at very high peak intensity (∼1 TW/cm2). Here, we demonstrate 3D printing based on triplet–triplet-annihilation photopolymerization (TTAP), which achieves submicron resolution while using a continuous visible LED light source with comparatively low light intensity (∼10 W/cm2). TTAP enables submicrometer feature sizes with exposure times of ∼0.1 s/voxel without requiri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
79
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(80 citation statements)
references
References 62 publications
1
79
0
Order By: Relevance
“…As a quadratic process, similar to TPP, TTA-UC is found to be able to trigger photopolymerization only at the focal point of the excitation beam (Figure c,d) . The first example of TTA-UC mediated 3D printing utilized the pair of palladium­(II) octaethylporphine (PdOEP) and 9,10-diphenylanthracene (DPA), which converts green light to blue light, to give 3D printing features as small as 0.6 ± 0.1 μm with a continuous green LED as excitation source (∼10 W cm –2 ). , In order to realize volumetric 3D printing with TTA-UC, systematic control over the threshold behavior of the upconversion materials is crucial since the quadratic relationship between input excitation and upconverted emission only exists below the threshold value. Furthermore, different printing schemes need distinct upconversion thresholds whereas a lower threshold is favorable for low-fluence rapid parallelized printing (Figure e) .…”
Section: New Applications Of Highly Efficient Nir Tta-ucmentioning
confidence: 99%
See 2 more Smart Citations
“…As a quadratic process, similar to TPP, TTA-UC is found to be able to trigger photopolymerization only at the focal point of the excitation beam (Figure c,d) . The first example of TTA-UC mediated 3D printing utilized the pair of palladium­(II) octaethylporphine (PdOEP) and 9,10-diphenylanthracene (DPA), which converts green light to blue light, to give 3D printing features as small as 0.6 ± 0.1 μm with a continuous green LED as excitation source (∼10 W cm –2 ). , In order to realize volumetric 3D printing with TTA-UC, systematic control over the threshold behavior of the upconversion materials is crucial since the quadratic relationship between input excitation and upconverted emission only exists below the threshold value. Furthermore, different printing schemes need distinct upconversion thresholds whereas a lower threshold is favorable for low-fluence rapid parallelized printing (Figure e) .…”
Section: New Applications Of Highly Efficient Nir Tta-ucmentioning
confidence: 99%
“…More interestingly, this reductive 1 [TTBP]* can be utilized to trigger the polymer- Very recently, TTA-UC has also been reported to be used for photopolymerization-based 3D printing. 18,19,43 Traditionally, to obtain high-resolution photopolymerization-based 3D printing, the technology of two photon polymerization (TPP) was required to be utilized because polymerization can be confined to the focal point of the pulsed laser light (60−100 nm in dimension). 44 However, the high power of the required femtosecond laser pulses (∼10 12 W cm −2 ) can lead to highcost of commercial instruments and limited print size and speed, which prevent the widespread application.…”
Section: Tta-uc Mediated Photoredox Catalysismentioning
confidence: 99%
See 1 more Smart Citation
“…This property has been leveraged to demonstrate TTA-UC-enabled volumetric 3D printing using violet or blue upconverted light. [29][30][31][32] The TTA-UC process is illustrated in Fig. 1A.…”
Section: Mainmentioning
confidence: 99%
“…Remarkably, the excitation power densities of these TTA-UC-assisted 3D printings were several orders of magnitude lower than those of two-photon-based 3D printings. Notably, when this article was under review, the Hayward group also found that porphyrin-based TTAP (entry 5 in Table 2 ) could be effectively utilized for high-resolution 3D printing (~100 nm) [ 96 ]. Doubtlessly, these studies not only present new applications for TTA-UC but also provide a novel approach for high-resolution 3D printing.…”
Section: Photochemistry Of Porphyrin-based Tta-uc For Chemical Transf...mentioning
confidence: 99%